Is Regression after Neoadjuvant Chemotherapy for Locally Advanced Breast Cancer Different in Sentinel and Non-sentinel Nodes? - KAYA, HANDAN (SPRINGER, 2018)
Tumor draining sentinel lymph nodes (SLNs) are the sites of selective changes as compared to non-SLNs. They show features of tumor-reactive lymphadenopathy, including increased total number of functional blood vessels, but a relative immunosuppressed status has also been described in them. We explored the hypothesis of a selective regression or non-regression in SLNs versus non-SLNs in 142 patients with 110 estrogen receptor-positive and 32 estrogen receptor-negative tumors undergoing both SLN biopsy and axillary lymph node dissection after neoadjuvant therapy by assessing the tumoral (metastatic) and regression statuses of SLNs and non-SLNs separately. Of the 89 cases with signs of nodal regression, 22 cases (25%) were in favor of a selective non-regression in SLNs, 18 cases (20%) were supportive of a selective and more pronounced regression in the SLNs and the remaining showed equal degrees of regression or non-regression in SLNs and non-SLNs. The results indicate that there is no obvious difference in the degree of regressive histological changes shown by SLNs and NSLNs. Therefore, this phenomenon may not be a major contributor to the higher false negative rate of SLN biopsy after neoadjuvant treatment.
Keywords: Sentinel lymph node; Non-sentinel lymph node; Breast cancer; Neoadjuvant therapy; Selective regression